Associations between resting state brain activity and A1 adenosine receptor availability in the healthy brain: Effects of acute sleep deprivation - Li, Changhong; Kroll, Tina; Matusch, Andreas; Aeschbach, Daniel; Bauer, Andreas; Elmenhorst, Eva-Maria; Elmenhorst, David (Frontiers in Neuroscience, 2023)
Previous resting-state fMRI (Rs-fMRI) and positron emission tomography (PET) studies shown that sleep deprivation (SD) affects both spontaneous brain activity and A1 adenosine receptor (A1AR) availability. Nevertheless, the hypothesis that the neuromodulatory adenosinergic system acts as regulator of the individual neuronal activity remains unexplored. Therefore, fourteen young men underwent Rs-fMRI, A1AR PET scans, and neuropsychological tests after 52 hours of SD and after 14 hours of recovery sleep. Our findings suggest higher oscillations or regional homogeneity in multiple temporal and visual cortices, whereas decreased oscillations in cerebellum after sleep loss. Meanwhile, we discovered increased connectivity strengths in sensorimotor areas whereas decreases in subcortical areas, and cerebellum. Moreover, negative correlations between A1AR availability and rs-fMRI metrics of BOLD activity in the left superior/middle temporal gyrus and left postcentral gyrus of the human brain provide insights into the molecular basis of neuronal responses induced by high homeostatic sleep pressure.